EFFECTIVE AND ECO-FRIENDLY STRATEGIES TO CONTROL BIRDS IN INDUSTRIAL ESTATE - Rahayu, Jasti; Hadi, Upik K; Soviana, Susi (UI Scholars Hub, 2025)
Bird infestations in industrial areas can cause infrastructure damage, contamination, and health risks. Despite these impacts, they are rarely addressed in environmental management strategies. At the Kaltim Industrial Estate (KIE) in Bontang, East Kalimantan, synanthropic bird species that thrive in human-altered environments have become persistent nuisances, particularly because of structural opportunities for roosting and altered ecological conditions. To address this issue, this study applied Integrated Pest Bird Management (IPBM), a non-lethal and environmentally friendly approach that combines species identification, behavior analysis, and targeted deterrents. IPBM was selected for its adaptability to industrial settings and its alignment with sustainable development goals. This study conducted from January to July 2024 at KIE, Riksa Gatra Prima, in collaboration with Institute Pertanian Bogor (IPB). Veterinary and Medical Entomology Laboratory. The Birds were identified based on their morphological features and vocalizations. Three nonlethal control methods: predator sound playback, laser pointers, and net installations, which were selected for their previous use in wildlife control and low ecological impacts. The data were descriptively analyzed and supported by visual documentation. The Asian glossy starling (Aplonis panayensis) was identified as the sole pest species with a density of 13 individuals per meter. Its success is attributed to its territoriality, adaptability, and social roosting. Predator sounds and lasers were ineffective (0%), whereas net installations achieved complete bird exclusion (100%) over 14-day period. Although limited to one species and site, the findings demonstrate the effectiveness of netting as a scalable, eco-friendly deterrent. This method can be integrated into environmental frameworks, such as the Environmental Management and Monitoring Plan (EMMP) and ISO 14001, to support sustainable operations and biodiversity protection in industrial zones.